COMPETITIVENESS ANALYSIS OF COPPER EXPORTS TO CHINA: CASE STUDY OF ASEAN COUNTRIES - Daniel Bonartua Malau; Nurmah Fudzah; Kashari; Jasella Sakwi Yanti; Hastuti (RADJA PUBLIKA, 2025)
This study analyzes the competitiveness of ASEAN copper exports (HS 7408) to the Chinese market over the period 2019–2023. China is one of the world’s largest copper importers, and ASEAN has emerged as a major supplier with substantial export value growth in recent years. Using secondary data from Trademap and World Integrate Trade Solution, the research applies quantitative descriptive methods supported by Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), and Export Product Dynamics (EPD) to assess the comparative position and market dynamics of copper exports from six ASEAN countries—Indonesia, Malaysia, Thailand, Philippines, Singapore, and Vietnam. The findings indicate varying levels of comparative advantage among ASEAN exporters, reflecting differences in productivity, export structure, and market integration. The analysis also highlights shifts in China’s import demand that influence ASEAN’s export performance and long-term prospects. Overall, the study provides insights into policy implications for strengthening ASEAN’s competitiveness in the Chinese copper market, particularly through enhancing productivity, export diversification, and value-added development.